Glycemic control and its associated factors among diabetic heart failure outpatients at two major hospitals in Jordan. - Anan S Jarab; Walid A Al-Qerem; Hanan Hamam; Shrouq Abu Heshmeh; Sayer Al-Azzam; Tareq L Mukattash; Eman A Alefishat (PLoS ONE, 2023)
Patients with heart failure (HF) are generally at higher risk of developing type 2 diabetes and having uncontrolled blood glucose. Furthermore, the prevalence of uncontrolled blood glucose in patients with HF is largely unknown. Identifying the factors associated with poor blood glucose control is a preliminary step in the development of effective intervention programs. The current cross-sectional study was conducted at two major hospitals to explore the factors associated with blood glucose control among patients with heart failure and type 2 diabetes. In addition to sociodemographic, medical records were used to collect medical information and a validated questionnaire was used to evaluate medication adherence. Regression analysis showed that poor medication adherence (OR = 0.432; 95%CI 0.204-0.912; P<0.05) and increased white blood cells count (OR = 1.12; 95%CI 1.033-1.213; P<0.01) were associated with poor glycemic control. For enhancing blood glucose control among patients with HF and diabetes, future intervention programs should specifically target patients who have high WBC counts and poor medication.